2007
DOI: 10.1021/np060587g
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Naphthoquinone Derivatives from the Twigs of Avicennia marina

Abstract: In a continuing search for novel bioactive compounds from marine mangrove plants, seven new naphthoquinone derivatives were isolated from Avicennia marina, namely, avicennone A (1), avicennone B (2), avicennone C (3), avicennone D (4), avicenone E (5), avicennone F (6), and avicennone G (7), along with the known compounds avicequinone A (8), stenocarpoquinone B (9), avicequinone C (10), avicenol A (11), and avicenol C (12). The chemical structures of 1-7 were elucidated by spectroscopic methods. Compounds 8-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 16 publications
0
56
0
2
Order By: Relevance
“…As Table 4, a total of 14 flavonoids including flavones, 19 naphthalene derivatives, 5 terpenoids, 7 steroids, 23 tannins 6 fatty acids, 31 glucosides from wide variety of secondary metabolite classes have been listed to date in genus Avicennia (Majumdar et al 1981;Sharaf et al 2000;Jia et al 2004;Feng et al 2007). Phytochemical studies have revealed that most chemically investigated Avicennia species till now are rich in phytochemicals, namely terpenoids, glucosides and naphthalene derivatives (Konig & Rimpler 1985;Sutton et al 1985;Shaker et al 2001;Han et al 2007). These naturally occurring compounds are found to be concentrated in the plant's leaf, stem/bark and aerial roots.…”
Section: Phytochemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…As Table 4, a total of 14 flavonoids including flavones, 19 naphthalene derivatives, 5 terpenoids, 7 steroids, 23 tannins 6 fatty acids, 31 glucosides from wide variety of secondary metabolite classes have been listed to date in genus Avicennia (Majumdar et al 1981;Sharaf et al 2000;Jia et al 2004;Feng et al 2007). Phytochemical studies have revealed that most chemically investigated Avicennia species till now are rich in phytochemicals, namely terpenoids, glucosides and naphthalene derivatives (Konig & Rimpler 1985;Sutton et al 1985;Shaker et al 2001;Han et al 2007). These naturally occurring compounds are found to be concentrated in the plant's leaf, stem/bark and aerial roots.…”
Section: Phytochemistrymentioning
confidence: 99%
“…These naturally occurring compounds are found to be concentrated in the plant's leaf, stem/bark and aerial roots. A number of pharmacologically important phyto-constituents belonging to different classes of phytochemicals which have been isolated include flavonoids (3) (Konig et al 1994;Gonzales et al 2000;Ramirez & Roa 2003;Han et al 2007Han et al , 2008Manilal et al 2009, Sumithra et al 2011bHossain et al 2012;Mahera et al 2013;Jain et al 2014;Ramanjaneyulu et al 2015). A detailed report on their occurrence, chemical structure and bioactivity has been presented in Table 5.…”
Section: Phytochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…From the leaves of A. marina collected in Beihai, Guangxi province, Jia et al [9] also isolated two naphthoquinone derivatives identified as avicequinone B (12) and avicequinone C (13). In 2007, Han et al [13] reported seven unusual naphthoquinone derivatives were isolated from the twigs of A. marina collected in Xiamen province, namely, avicennone A-G (14)(15)(16)(17)(18)(19)(20), along with the known compounds avicequinone A (21), stenocarproquinone B (22), avicequinone C (13), avicenol A (23), and avicenol C (24).…”
Section: Naphthalene Derivativesmentioning
confidence: 99%